If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + -1) = 2(y + -4) + -6 Reorder the terms: 5(-1 + y) = 2(y + -4) + -6 (-1 * 5 + y * 5) = 2(y + -4) + -6 (-5 + 5y) = 2(y + -4) + -6 Reorder the terms: -5 + 5y = 2(-4 + y) + -6 -5 + 5y = (-4 * 2 + y * 2) + -6 -5 + 5y = (-8 + 2y) + -6 Reorder the terms: -5 + 5y = -8 + -6 + 2y Combine like terms: -8 + -6 = -14 -5 + 5y = -14 + 2y Solving -5 + 5y = -14 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -5 + 5y + -2y = -14 + 2y + -2y Combine like terms: 5y + -2y = 3y -5 + 3y = -14 + 2y + -2y Combine like terms: 2y + -2y = 0 -5 + 3y = -14 + 0 -5 + 3y = -14 Add '5' to each side of the equation. -5 + 5 + 3y = -14 + 5 Combine like terms: -5 + 5 = 0 0 + 3y = -14 + 5 3y = -14 + 5 Combine like terms: -14 + 5 = -9 3y = -9 Divide each side by '3'. y = -3 Simplifying y = -3
| 9y-6x=3+5x | | 7s-(3s+1)=4(s+s) | | -2(n-5)+4n=17 | | -(-x+w)-2(-4w+5x)= | | F(x)=4x+10F(2) | | sqrt(3x+1)-sqrt(x-1)=2 | | 4a+3=7a-16 | | 80=11c+32 | | 1/2+(2/3/3/4)-4/5*5/6= | | 4y-8-3y=2y-12 | | 8x+7=12-2x | | 17x-3+17x+8= | | 66=-3(3n-4) | | 3x^4-30x^2+27= | | 3x+10=x+29 | | 7.06=.36x+(35.3+-1.85x) | | 3n-8=52 | | 3n-8=53 | | 22-d=17 | | 6x+5=-36+4x | | -3u+1+7w=4w+4-5 | | 51-(-6)=-4x+12-x | | 24a-22=4(6a-1) | | 4n-8=-24 | | 16=1.8+32 | | 7.06=.37x+.20a | | (8-2)+24*12= | | 45x-16x^2=10 | | 2x^2+4xy+2y^2-5x+4y+7=0 | | 4x-B(x+1)(x+1)+4x=4-Bx^2 | | -6x-6+8x=2x-6 | | 17-7=-32 |